Managing with power : politics and influence in organizations - Pfeffer, Jeffrey (Boston, Mass. : Harvard Business School Press, 1992)
Although much has been written about how to make better decisions, a decision by itself changes nothing. The big problem facing managers and their organizations today is one of implementation--how to get things done in a timely and effective way. Stanford Business School Professor Jeffrey Pfeffer argues that problems of implementation are really issues of how to influence behavior, change the course of events, overcome resistance, and get people to do things they would not otherwise do. In a word, power.
Includes bibliographical references (p. 367-377) and index.
Keywords: Decision-making.; Power (Social sciences); Organizational behavior